PEMANFAATAN TEKNOLOGI IoT UNTUK MENDUKUNG PEMBELAJARAN INTERAKTIF DAN PENGELOLAAN SARANA PRASARANA DI LEMBAGA PENDIDIKAN ISLAM - Mushofa, Mushofa; Cahyadi Maseri, Ani (Penerbit Lafadz Jaya, 2025)
This study examines the utilization of Internet of Things (IoT) technology as an innovation to support interactive learning and the management of facilities and infrastructure in Islamic educational institutions. In the digital era, IoT enables automatic connectivity among devices, which can improve the quality of learning and enhance the efficiency of educational facility management. The method employed is a literature study with a content analysis approach applied to scientific literature, books, and indexed journals. The findings indicate that IoT is applied in various aspects such as smart classrooms, automatic attendance systems, energy management, and sensor-based security. The use of IoT aligns with Islamic educational values when accompanied by principles of Islamic digital literacy and ethics. However, challenges include limited infrastructure, high costs, low digital literacy, and data security concerns. Therefore, an integrative strategy is needed, including human resource capacity building, multisectoral partnerships, and the formulation of technology policies based on Islamic values. The findings are expected to provide a conceptual contribution to the development of adaptive and sustainable Islamic education models in response to the demands of the industry 4.0 revolution.